Bridging the Gap between Bisylides and Methandiides: Isolation, Reactivity, and Electronic Structure of an Yldiide1. Issue 29 (10th June 2015) - Scherpf, Thorsten; Wirth, Regina; Molitor, Sebastian; Feichtner, Kai‐Stephan; Gessner, Viktoria H.
Abstract Bisylides and methandiides are two unique families of carbon bases that have found a variety of applications in recent years. Metalated ylides (yldiides) are the link between these types of compounds. Yet, only little is known about their properties, reactivities, and particularly their electronic structure. Here, we report the preparation of the metalated ylide [Ph3P‐C‐SO2Tol]− (1) with different alkali metal counterions. The compounds have been studied by X‐ray diffraction analysis and NMR spectroscopy and the first structures of a sodium and potassium yldiide are presented. The electronic structure of 1 was explored by DFT calculations confirming its relation with other divalent carbon species. Reactivity studies demonstrate the strong nucleophilicity of the yldiide and its capability to act both as a σ‐ and π‐donor.